Rancangan tempatan daerah Bentong, Pahang 2035 (Penggantian) - Asmawi, M. Zainora (PlanMalaysia, 2019)
The local plan is prepared to replace the present Local Plan. It covers the development strategies and proposal plans for district of Bentong, ranging from land use until environment. It has gone through the process of analysis and recommendation following the national framework of preparing Local Plan under the purview of PlanMalaysia@Pahang. Environmental sector is one of the essential components, covering the quality of air, water, noise and environmental sensitives areas.